Evaluation of Anti-bacterial Activity of Gold Nanoparticles in-vitro - Mohammed Abbas Farman; Walaa Najm Abood (Diyala Journal for Veterinary Sciences, 2024)
Gold nanoparticles were used in recent years in different applications for medicinal purposes. The dominant traits of GNPs include a great surface area, optoelectronic properties, limited toxicity, and excellent biocompatibility. The aim of this study was to investigate the antibacterial activity of gold nanoparticles. In this study bacterial isolates from humans and animals were applied to investigate the anti-bacterial effect of gold nanoparticles by using well diffusion method with different doses of gold nanoparticles solution. The result was shown that gold nanoparticles solution has anti-bacterial effect through the inhibition zone of bacterial species growth of E. coli, Staphylococcus spp., Streptococcus spp. and Serratia spp. isolated from humans and E.coli, Staphylococcus spp. isolated from animals treated with gold nanoparticles at doses of 10 μg /mL and 20 μg /mL. The conclusion: Gold nanoparticles have anti-bacterial activity for different bacterial species that may be used in the future in the pharmacological applications and treatment of diseases.